Musso’s Role in the PKI Rebellion in Madiun in 1948 - Afrianto, Muhammad Ridzky; Wibowo, Tubagus Umar Syarif Hadi; Ribawati, Eko (UNIVERSITAS MUHAMMADIYAH METRO, 2024)
This research aims to find out how Musso started the PKI rebellion in Madiun, the beginning of Musso's involvement in the PKI rebellion in Madiun and the end of Musso's journey in the PKI rebellion in Madiun in 1948. This research method is historical with a literature study approach. The results of this research stated that Musso had aspirations to make Indonesia a Soviet country, before heading to Indonesia, a discussion was held first between Musso, Soeripno, and Paul De Groot to discuss the formulation of the strategy of communism in Indonesia. Musso also chose a radical path to turn Indonesia into a Soviet State and then the formulation was perfected and named as Jalan Baru. Seeing the opportunity during the destruction of Amir Syarifuddin's Cabinet and building an opposition party dominated by the left. The arrival of Musso with a new idea, namely the New Way and attracted the left. With the existence of this People's Democratic Front organization, it makes it easier to spread communist ideology in Indonesia by door to door and holding speeches in the field to attract sympathizers to join the communists. The leftists immediately spread their members to the surrounding areas of Central Java, East Java, and Yogyakarta to attract new members. When the rebellion began, President Soekarno immediately took action to immediately crush the PKI rebellion.